The 2.5-minute loaded repeated jump test: Evaluating anaerobic capacity in alpine ski racers with loaded countermovement jumps - Patterson, C.; Raschner, C.; Platzer, H. -P. (The Journal of Strength and Conditioning Research, 2014)
The purposes of this study were to test the reproducibility of the 2.5-minute loaded repeated jump test (LRJT) and to test the effectiveness of general preparation period (GPP) training on anaerobic fitness of elite alpine ski racers with the LRJT. Thirteen male volunteers completed 2 LRJTs to examine reliability. Nine male Austrian elite junior racers were tested in June and October 2009. The LRJT consisted of 60 loaded countermovement jumps (LCMJs) with a loaded barbell equivalent to 40% bodyweight. Before the LRJT, the power (P) of a single LCMJ was determined. Power was calculated from ground reaction forces. The mean P was calculated for the complete test and for each 30-second interval. The interclass correlation coefficients (between 0.88 and 0.99) for main variables of the LRJT demonstrated a high reliability. A repeated-measures analysis of variance indicated that anaerobic capacity was significantly higher in October (p < 0.05). The ski racers' single LCMJ P increased from 37.0 ± 1.2 W/kg to 39.0 ± 1.4 W/kg. The mean P of the total test improved from 33.6 ± 1.2 W/kg to 35.8 ± 1.3 W/kg, but relative effect of fatigue did not change. The GPP training improved the athletes' ability to produce and maintain muscular power. The LRJT is a reliable anaerobic test suitable for all alpine ski racing events because the 60 jumps simulate the approximate number of gates in slalom and giant slalom races and the 2.5 minutes is equivalent to the duration of the longest downhill race.